Student Responses to Biology E-Module Integrated Enrichment of Imtaq Values in the Material of the Indra System - Safitri, Yeni; Robiah, Siti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This study aims to determine students' responses to the electronic module product of sensory system material integrated with the values of faith and piety that have been developed. This research is research and development (R&D) using the modified Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, but this research only reaches the Development stage. Determination of the student sample by purposive sampling with a total sample of 60 students from 3 schools. Student responses were obtained through limited trials atSMAN 2 Siak Hulu, SMA Al Azhar Syifa Budi Pekaanbaru, and MA Al-Ihsan Boarding School, Data were collected through observation, documentation, interviews, and questionnaires. Data were analyzed descriptively. The results showed that the developed e-module received a very good response from students with an average of 92.14%. Thus the developed E-module can proceed to the large-scale trial stage. DOI: http://dx.doi.org/10.23960/jbt.v11.i2.28433